2019
DOI: 10.1111/trf.15610
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study of platelet concentrates photochemically treated with amotosalen and UVA light for pathogen inactivation

Abstract: BACKGROUND: The risk of bacterial contamination and the deterioration of platelet (PLT) quality limit the shelf-life of platelet concentrates (PCs). The INTERCEPT pathogen inactivation system reduces the risk of pathogen transmission by inhibiting nucleic acid replication using a combination of a photo-reactive compound and UVA illumination. The goal of this study was to investigate the effects the INTERCEPT system has on the PLT metabolome and metabolic activity.From the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…A decrease in CCI with or without impact on PC consumption has been reported [1‒3]. This observation might be explained by an increase of PS expression, platelet activation, and GPIb shedding, as mentioned in Introduction [4‒17]. The activation of the MAPK pathway is in agreement with this phenotype, where p38 phosphorylation is induced by amotosalen/UVA treatment and related to PS expression and GPIb shedding that primes this receptor for cleavage.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A decrease in CCI with or without impact on PC consumption has been reported [1‒3]. This observation might be explained by an increase of PS expression, platelet activation, and GPIb shedding, as mentioned in Introduction [4‒17]. The activation of the MAPK pathway is in agreement with this phenotype, where p38 phosphorylation is induced by amotosalen/UVA treatment and related to PS expression and GPIb shedding that primes this receptor for cleavage.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, these photochemical or photo-treatments modify the phenotype and functions of platelets to different extents. Compared to untreated PCs, increased p-selectin expression (platelet activation), exposure of phosphatidylserine (marker of senescence), decrease in GPIb expression (von Willebrand receptor), activation of integrin αIIbβ3 (fibrinogen receptor), modulation of aggregation responses (function of agonists), and modification of metabolite levels have been reported [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Possible causes are protein degradation caused by UV-light exposure [ 68 ] or incubation with the compound absorption device. Our group has shown that specific metabolite species show a significant concentration drop after PI processing, especially after the compound absorption phase [ 69 ]. The decrease in levels of specific proteins can be beneficial for patients, especially if these proteins have been implicated in transfusion reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical clustering was performed using Euclidean distance and Ward’s method. Principal components analysis (PCA), a dimensionality reduction technique used to preserve as much of the variance of data as possible in lower-dimensional output [ 69 ], was performed using R v3.5.1 (R Development Core Team).…”
Section: Methodsmentioning
confidence: 99%
“…Intra- and extracellular samples were analysed by hydrophilic interaction liquid chromatography [HILIC] coupled with time-of-flight (TOF) mass spectrometry (Synapt G2, Waters, UK) using a previously described method 23 . Each sample was measured both in positive and negative ionization mode.…”
Section: Methodsmentioning
confidence: 99%